The perception and experiences of pregnant women facing the COVID-19 epidemic: A Qualitative study - Roghieh Bayrami; Samira Ebrahimi (Mashhad University of Medical Sciences, 2021)
Introduction: Pregnant women are one of the main groups that should be considered during the Covid-19 pandemic. By knowing the pregnant women's worrying experiences in this period, we can achieve the strategies to improve the health and quality of life and to plan for improving prenatal care. This study was performed with aim to explore the perception and experience of pregnant women in the face of COVID 19 pandemic. Methods: This qualitative study was carried out in Comprehensive Health Services centers in Urmia-Iran during May to October 2020. Data were collected using 14 individual in-depth semi-structured telephone interviews. Participants were selected among pregnant women through purposeful sampling, until data saturation was reached. Data were analyzed through conventional content analysis approach using the MAXQDA software (version 10). Results: From analyzing data, 580 primary codes and four main categories including: "lifestyle change(change in daily activities, isolation and social distancing), "experienced psychological effects" (pregnancy health concerns, fear of family members getting sick, financial stress and confusion over information dissemination), "seeking support" (need of support from relatives, need of support from health personnel), and "change in the prenatal care process"(not referring to government centers, reduction in number of prenatal care)were emerged. Conclusion: The covid-19 pandemic has significant potential in changing lifestyle, routine prenatal care and psychological status in pregnant women. Therefore, it is necessary for midwives to provide virtually and by telephone the necessary training and counseling about self-care and reducing anxiety and stress for pregnant women.